Streeter Dysplasia, from Pelvic to Digits: A Case Report - Komang Agung Irianto Suryaningrat, NIDN. 8819130017 (DiscoverSys, 2016)
Background: Streeter dysplasia is a term to describe fetal congenital syndrome which mainly characterized by constriction band on appendages, prenatal amputations of extremities, and acrosyndactyly. This syndrome has wide range of clinical manifestation between patients, as reflected by many other terms to describe this syndrome. Case: The author reported five cases of Streeter dysplasia with constriction band on different locations of the body, with a patient having a constriction band around pelvic and other multiple anomalies, patient with constriction around leg and caused acute limb ischemic, and several cases of acrosyndactyly around hand and foot. Result and Conclusion: Constriction band release surgery, as well as correction surgery for other abnormality was performed, either by direct closure or Z-plasty with satisfactory result in functional and aesthetic.